Comparison of the Middle Miocene and the Upper Miocene source rock formations in the Sava Depression (Pannonian Basin, Croatia) - Troskot-Čorbić, Tamara (Array, 2009)
Summary: The Sava Depression lies at the very south-western margin of the Pannonian Basin. There are 20 hydrocarbon fields altogether and 17 are still in production. The organic geochemistry data and their statistical analysis from the 25 exploration wells, indicate source rock formations in two stratigraphic levels, an older one of Middle Miocene age (Badenian and Sarmatian) and a younger one of Upper Miocene age (Lower Pannonian). Both source rock formations are composed of marls, calcitic marls, clayey limestones and shales. Source rock intervals lay at depths from 1200 to 3362 m. The Total Organic Carbon (TOC) of analyzed samples varies from 0.39 to 4.94%, while their total generative hydrocarbon potential is from 2.40 to 37.40 mg HC/g rock. The mean thickness of the intervals is 100–150 m. There is a regular linear increase of the maturity level with depth. Source rocks are mature, in the catagenetic phase of transformation that enables hydrocarbon generation. A favourable organic facies, mostly kerogen type II, (organic facies AB and B), with good hydrocarbon potential, dominates the north-western and central part of the depression. It can be connected with the deeper parts of the depression and/or protected, anoxic to dysoxic stagnant environments with a gradual transition from marine (Badenian/Sarmatian) to brackish depositional environments (Lower Pannonian). In the south-eastern part of the depression, the dominant kerogen type is II–III, (organic facies BC), which indicates a stronger influx of terrestrial material from the uplifted parts that are generally closer to the margins of the depositional basin. The Fisher test (F-test) of the variance similarity (homogeneity), clearly indicates that the Badenian/Sarmatian samples belong to a statistically different population from the Lower Pannonian ones, due to their different depositional environments